Evolusi Lanskap Budaya Tamansari Yogyakarta - Ramadanti, Aulia Shabrina; Soetrisno, Endang Triningsih (Jurnal Lanskap Indonesia, 2024)
Kota Yogyakarta, known for its cultural richness and sovereignty, displays its cultural heritage characteristics through Keraton Yogyakarta’s heritage object. Tamansari is Keraton Yogyakarta’s cultural complex built for the royal family’s leisure. For 258 years, Tamansari Complex’s cultural landscape has been undergoing transformation. The transformations trigger the evolutional process of the Tamansari Complex’s cultural landscape identity. This thesis investigates the evolutional process of Tamansari Complex’s cultural landscape in 1765 - 2023. Cultural Landscape Evolution theory acts as the analysis method of this thesis research. The research time spans from January - August 2023. This research is the first attempt to view the Tamansari Complex from the perspective of cultural landscape focusing on the evolutional process of the Tamansari Complex’s cultural landscape identity.